2018
DOI: 10.3390/ijms19082205
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Tumor Suppressive Properties of Melatonin

Abstract: There is considerable evidence that melatonin may be of use in the prevention and treatment of cancer. This manuscript will review some of the human, animal and cellular studies that provide evidence that melatonin has oncostatic properties. Confirmation that melatonin mitigates pathogenesis of cancer will be described from both direct study of its effects on carcinogenesis, and from indirect findings implicating disruption of the circadian cycle. A distinction is made between the role of melatonin in preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 117 publications
0
51
0
2
Order By: Relevance
“…Melatonin is highly pleiotropic and regulates countless physiological parameters in numerous organs. 8,[28][29][30][31] Among them, several fields deserve particular emphasis, such as the control of circadian rhythms and, in photoperiodically sensitive species, of seasonality, both in conjunction with the transmission of the signal "darkness" [32][33][34] ; modulation of differentiation and growth [35][36][37] ; antioxidative protection by various mechanisms [38][39][40][41][42] ; anti-oncogenic and oncostatic actions [43][44][45] ; and, with particular relevance to this article, immune modulation. 16,[46][47][48][49] Physiological functions of macrophages go from host defense to immune downregulation, 50,51 in addition to their homeostatic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is highly pleiotropic and regulates countless physiological parameters in numerous organs. 8,[28][29][30][31] Among them, several fields deserve particular emphasis, such as the control of circadian rhythms and, in photoperiodically sensitive species, of seasonality, both in conjunction with the transmission of the signal "darkness" [32][33][34] ; modulation of differentiation and growth [35][36][37] ; antioxidative protection by various mechanisms [38][39][40][41][42] ; anti-oncogenic and oncostatic actions [43][44][45] ; and, with particular relevance to this article, immune modulation. 16,[46][47][48][49] Physiological functions of macrophages go from host defense to immune downregulation, 50,51 in addition to their homeostatic activities.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between melatonin and disease is apparent in: (a) affecting its endogenous melatonin levels, particularly the inhibition of the secretory nocturnal peak by excessive lighting at dark time in response to ocular signals, the so‐called “light‐at‐night idea” or LAN hypothesis of Stevens; or (b) disrupting its membrane receptor‐mediated signaling and/or receptor‐independent activities. Concomitantly, the link between circadian alterations (eg, rotating shift work or LAN), (epi)genetic changes, metabolic disorders, immune weakening, altered pattern of the human plasma proteome during circadian misalignment, and the aggravation of cancer risk is a highly discussed health issue, which consequently has generated ample epidemiologic and experimental literature . In this sense, recent additional studies have enriched the epidemiological evidence linking shift work and augmented CRC risk.…”
Section: Epidemiology Of Crc: the Positive Impacts Of Melatoninmentioning
confidence: 99%
“…Regarding this issue, under real physiological conditions the feasibility of some of the direct effects (nonreceptor mediated) shown by melatonin have recently been questioned. In experimental systems, the verification of melatonin actions is usually carried out at concentrations higher (millimolar range) than those reached inside cells and tissues, which, according to the currently available evidence, does not exceed the picomolar/nanomolar range . Thus, it is believed that some of the direct effects reported in the clinical literature could be artifacts forced by melatonin concentrations much higher than cellular amounts and, consequently, it is suggested that most of the oncostatic mechanisms activated by physiological melatonin activity are mediated by its specific receptors.…”
Section: Melatonin Receptors‐mediated Effects In Crcmentioning
confidence: 99%
“…In an in vitro study, melatonin suppressed the growth of human cancer cell lines by inhibition of specific phases of cell cycles. Also, melatonin decreases metastasis and invasion by changing the expression of adhesion molecules and intracellular communication . Other oncostatin actions of melatonin in various cancers include the modulation of transactivation and expression of estrogen receptor (ERa), calcium/calmadulin and protein kinase C activity, cytoskletal structure, redox status of cells, the activity of aromatase and telomerase, and fatty acid transportation and metabolism …”
Section: Anticancer Features Of Melatoninmentioning
confidence: 99%
“…Also, melatonin decreases metastasis and invasion by changing the expression of adhesion molecules and intracellular communication. 68,77,78 Other oncostatin actions of melatonin in various cancers include the modulation of transactivation and expression of estrogen receptor (ERa), calcium/calmadulin and protein kinase C activity, cytoskletal structure, redox status of cells, the activity of aromatase and telomerase, and fatty acid transportation and metabolism. 70,[79][80][81][82] Besides the direct action of melatonin, this agent enables neutralizing free radicals through induction of suppression of redox enzyme activity (DUOX1&2, NOX2&4, iNOS, and mitochondria derived ROS) or antioxidant enzymes.…”
Section: Anticancer Features Of Melatoninmentioning
confidence: 99%